Stimulator of Interferon Genes Promotes Host Resistance Against Pseudomonas aeruginosa Keratitis - Chen, Kang; Fu, Qiang; Liang, Siping; Liu, Yiting; Qu, Wenting; Wu, Yongjian; Wu, Xinger; Wei, Lei; Wang, Yi; Xiong, Yujuan; Wang, Weijia; Wu, Minhao (Frontiers in Immunology, 2018)
Pseudomonas aeruginosa (PA) is the leading cause of bacterial keratitis, especially in those who wear contact lens and who are immunocompromised. Once the invading pathogens are recognized by pattern recognition receptors (PRRs) expressed on the innate immune cells, the innate immune response is stimulated to exert host defense function, which is the first line to fight against PA infection. As a converging point of cytosolic DNA sense signaling, stimulator of interferon genes (STING) was reported to participate in host-pathogen interaction. However, the role of STING in regulating PA-induced corneal inflammation and bacterial clearance remains unknown. Our data demonstrated that STING was activated in murine model of PA keratitis and in in vitro cultured macrophages, indicated by western-blot, immunostaining and flow cytometry. To explore the role of STING in PA keratitis, we used siRNA to silence STING and 2’3’-cGAMP to activate STING in vivo and in vitro, and the in vivo data found out that STING promoted host resistance against PA infection. To investigate the reason why STING played a protective role in PA keratits, the inflammatory cytokine secretion and bacterial load were measured by using real-time PCR and bacterial plate count, respectively. Our data demonstrated that STING suppressed the production of inflammatory cytokines and enhanced bacterial elimination in murine model of PA keratitis and in PA-infected macrophages. To further investigate the mechanism beneath, the phospharylation of mitogen-activated protein kinase (MAPK), the nuclear translocation of nuclear factor-κB (NF-κB) and the bactericidal mechanism were measured by western-blot, immunofluorescence, and real-time PCR, respectively. Our data indicated that STING suppressed inflammatory cytokine expressing via restraining NF-κB activity, and enhanced inducible NO synthase (iNOS) expression, an oxygen-dependent bactericidal mechanism. In conclusion, our study demonstrated that STING promoted host resistance against PA keratitis and played a protective role in PA-infected corneal disease, via inhibiting corneal inflammation and enhancing bacterial killing.